Treatment of dorsal fracture-dislocation of the proximal interphalangeal joint using the Ligamentotaxor device: clinical and radiographic preliminary results - Kostoris, Francesco; Canton, Gianluca; Longo, Emiliano; Romano, Francesco; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Fracture-dislocations of the proximal interphalangeal joint are complex injuries, often difficult to treat. Several treatment options have been described. Among them dynamic external fixation proved to be a safe technique leading to good results in many authors experience. The principles of this treatment are to avoid edema, prevent stiffness and tendon adhesions, promote joint remodelling and facilitate rehabilitation. The Ligamentotaxor® device is a simple and reproducible dynamic external fixation system that has been used in recent years to treat proximal interphalangeal joint fracture-dislocations, with favourable results. The aim of the present study is to evaluate our preliminary results with the Ligamentotaxor® device for treatment of these complex lesions. Methods: Four patients between December 2015 and January 2017 were treated at our institution with the Ligamentotaxor® device. Clinical and radiographic results were evaluated at mean 6 months follow-up. Results: Clinical results were meanly good and appeared to be comparable to most recent literature. Mean range of motion was 60,5°, mean extension lag 18,5°. Mean QuickDASH and Michigan Hand Questionnaire scored 21.6 and 72 respectively. Radiographic evaluation showed fracture healing in all cases. No relevant complications were noted. Conclusion: The Ligamentotaxor® device is simple to implant, provides good stability and allows an immediate gentle active movement. According to present work the preliminary results are encouraging.